A New Rival State? Australia in Tsarist Diplomatic Communications - Massov, Alexander; Pollard, Marina; Windle, Kevin (ANU Press, 2018)
"A New Rival State? is a unique collection of dispatches written in 1857-1917 by the Russian consuls in Melbourne to the Imperial Russian Embassy in London and the Russian Foreign Ministry in St Petersburg. Written by eight consuls, they offer a Russian view of the development of the settler colonies in the late nineteenth century and the first years of the federated Commonwealth of Australia. They cover the federalist movement, the changing domestic political situation, labour politics, the treatment of the Indigenous population, the 'White Australia' policy, Australia's defensive capacity and foreign policy as part of the British Empire. The bulk of the material is drawn from the Russian-language collection The Russian Consular Service in Australia 1857-1917, edited by Alexander Massov and Marina Pollard (2014), using documents from the archive of the Russian Foreign Ministry."